Pilihan Rasional Petani Padi Miskin di Kabupaten Ngawi Pada Musim Paceklik - Sukma, Panggih Setyaning; Handoyo, Pambudi; Agustin, Dewien (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This research analyzes the rational choices of impoverished rice farmers in Ngawi Regency during paceklik, a critical period with no income from harvests. Using qualitative methods and James Coleman's Rational Choice Theory, this study identifies the farmers' strategies in extreme limitations. Farmers are proven to be rational actors who prioritize survival, manifested in: 1) tight spending control and personal food reserves; 2) seeking supplementary work; 3) taking on "pay-one-debt-with-another" loans for urgent needs and production capital; and 4) utilizing social capital from family networks. These choices, though often risky and perpetuating the cycle of poverty, are the farmers' optimal decisions for survival amidst structural constraints. This research affirms that rationality must be understood from the actor's perspective, not an external one, and emphasizes the importance of relevant policies to enhance the resilience of impoverished farmers.